Handbook of social psychology - Delamater, John (Springer, 2017)
Part 1: Theoretical Perspectives. Part 2: Development and Socialization. Part 3: Intrapersonal Processes. Part 4: Interpersonal Processes. Part 5: The individual in sociocultural context.